Antioxidant conductive silver paste for automobile glass and preparation method thereof
By combining spherical silver powder with sheet silver powder and silver powder with different tap density in the conductive silver paste for automotive glass, combined with the optimization of organic additives and glass powder, the problem of degradation of conductive silver paste after oxidation is solved, and an anti-oxidation conductive silver paste for automotive glass with high oxidation resistance and conductivity is achieved.
Patent Information
- Application Number
- CN202411977961.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
The conductive silver paste for existing automotive glass decreases after oxidation, which affects the heating effect and the beautiful appearance of the vehicle, and lacks anti-oxidation properties.
The combination of spherical silver powder and sheet silver powder is used to combine silver powder with different tap density, and the composition and process flow of silver paste is optimized by reasonably selecting organic additives and glass powder, and the composition and process flow of silver paste are prepared for automotive glass with antioxidant properties.
It significantly improves the oxidation resistance and conductivity of silver paste, delays the oxidation process of the silver layer, enhances its performance stability in harsh environments, and meets the requirements of conductivity, adhesion and matching with black glaze.
Smart Images

Figure BDA0005220871930000041 
Figure BDA0005220871930000051 
Figure BDA0005220871930000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silver paste for automobile glass, and in particular to an anti-oxidation conductive silver paste for automobile glass and a preparation method thereof. Background Art
[0002] The rapid development of the global electronics industry has driven the continuous growth of the market demand for conductive silver paste. The rapid development of smart phones, computers, automotive electronics, photovoltaics and other fields has increased the demand for conductive silver paste. The scale of China's conductive silver paste market has grown significantly, jumping from 36.175 billion yuan to 94 billion yuan in 2023, with an impressive annual growth rate.
[0003] With the rise of the electronics industry, conductive silver paste has begun to be used in semiconductors, printed circuit boards and other fields. With the advancement of science and technology, its application field has been continuously expanded to emerging industries such as new energy and biomedicine. This places strict requirements on the performance of conductive silver paste. Among them, the use of conductive silver paste on automotive glass pays more attention to its anti-oxidation performance. The silver wire on the automotive glass is mainly used for heating to quickly defrost and defog. Oxidation will cause the conductivity of the silver wire to decrease, affecting the heating effect, thereby reducing the comfort and safety of the car. In addition, the silver decorative strips around the car windows will appear indelible spots after oxidation, causing the silver strips to appear pale or grayish white, affecting the appearance of the vehicle.
[0004] Chinese patent CN101613186A discloses lead-free silver paste for high-temperature sintering automobile glass heating wire and its preparation method, the lead-free silver paste includes the following components and contents (by weight): silver powder 50% to 85%; lead-free silver glass powder 3% to 7%; polymer adhesive 3% to 12%; organic solvent 7% to 23%; ultrafine metal compound 1% to 5%; additive 0.5% to 3%, the components are mixed, dissolved, ground and filtered to obtain lead-free silver paste for high-temperature sintering automobile glass heating wire. However, it is not disclosed that it has anti-oxidation properties, and its application is subject to certain restrictions. Summary of the invention
[0005] The purpose of the present invention is to provide an antioxidant conductive silver paste for automotive glass and a preparation method thereof in order to improve the antioxidant property of the conductive silver paste, which can not only meet the technical index requirements of the existing automotive glass such as conductivity, adhesion, and matching with black glaze, but also has antioxidant properties.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide an anti-oxidation conductive silver paste for automotive glass, wherein the raw materials are the following components and weight percentage contents:
[0008] Spherical silver powder 50-80%, flake silver powder 8-10%; glass powder 1# 0.5-2.0%, glass powder 2# 0.5-2.0%, glass powder 3# 1.0-2.0%; dispersant 0.3-1%; thixotropic agent 0.1-0.5%; leveling agent 0.5-1.0%; polymer resin 2-10%; organic solvent 5-25%.
[0009] In some specific embodiments, the spherical silver powder has a particle size of 0.5-3.0 μm and a tap density of 5.0-7.0 g / mL;
[0010] The particle size of the flaky silver powder is 4-12 μm, and the tap density is 1.0-3.0 g / mL.
[0011] In some specific embodiments, the glass powder 1# is lead-free glass powder with a particle size of 1.2-3.3 μm, including the following components and weight percentages: 28% silicon dioxide, 6% niobium pentoxide, 0.5% iron oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, and 7.5% potassium oxide.
[0012] In some specific embodiments, the glass powder 2# is lead-free glass powder with a particle size of 0.5-2.1 μm, including the following components and weight percentages: 3% titanium dioxide, 5% molybdenum trioxide, 5% cobalt tetroxide, 6% vanadium pentoxide, 68% bismuth trioxide, 4% silicon dioxide, 5% aluminum oxide, and 4% zinc oxide.
[0013] In some specific embodiments, the glass powder 3# is lead-free glass powder with a particle size of 2.0-3.0 μm, including the following components and weight percentages: 11% silicon dioxide, 3% titanium dioxide, 4% a mixture of zinc oxide and aluminum oxide, 72% bismuth oxide, 7% boric acid, and 3% lithium carbonate, wherein the mass ratio of zinc oxide to aluminum oxide in the 4% mixture of zinc oxide and aluminum oxide is 1:1.
[0014] In some specific embodiments, the polymer resin is selected from any one or more of ethyl cellulose, nitro cellulose, and ethyl hydroxyethyl cellulose.
[0015] Preferably, the polymer resin is ethyl cellulose.
[0016] In some specific embodiments, the dispersant is selected from any one or more of polyvinyl alcohol, sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, tributyl phosphate, oleic acid, stearic acid and n-octanoic acid.
[0017] In some specific embodiments, the thixotropic agent is selected from any one or more of organic bentonite, modified polyurea compounds, fumed silica, acrylic resin, and polyamide wax.
[0018] In some specific embodiments, the leveling agent is selected from any one or more of silicone resin, hydrogenated castor oil, polyvinyl butyral, and polyacrylate;
[0019] The organic solvent is selected from any one of terpineol, turpentine, diethylene glycol butyl ether, diethylene glycol dibutyl ether, and butyl carbitol acetate, or a mixture of several of them.
[0020] The second technical solution of the present invention is to provide a method for preparing the anti-oxidation conductive silver paste for automobile glass as described in one of the above technical solutions, comprising the following steps:
[0021] S1. Prepare the materials according to the following components and weight percentages:
[0022] Spherical silver powder 50-80%, flake silver powder 8-10%; glass powder 1# 0.5-2.0%, glass powder 2# 0.5-2.0%, glass powder 3# 1.0-2.0%; dispersant 0.3-1%; thixotropic agent 0.1-0.5%; leveling agent 0.5-1.0%; polymer resin 2-10%; organic solvent 5-25%;
[0023] S2. Preparation of carrier: Weigh the polymer resin and the organic solvent, and then heat them to 80°C and keep the temperature constant. After the polymer resin is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, and obtain the carrier;
[0024] S3, preparation of silver paste: weigh spherical silver powder, flaky silver powder, glass powder 1#, glass powder 2#, glass powder 3#, dispersant, thixotropic agent, leveling agent, and fully mix with the carrier in a mixer, and then use a high-speed dispersant for high-speed dispersion to obtain a uniform slurry;
[0025] S4. Production of silver paste: Grind the above slurry in a three-roll mill, and fine-tune the fineness of the silver paste to below 15 μm and the viscosity to 20-30 Pa·S by rollers, so as to prepare an antioxidant conductive silver paste for automotive glass.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention realizes particle grading through an innovative combination of silver powder collocation and tap density, thereby increasing the film thickness of the silver layer on the overlap of the silver powder, which not only enhances the anti-oxidation performance, but also improves the conductive performance.
[0028] Specifically, by combining spherical silver powder with flaky silver powder and adjusting different tap densities, the contact between silver powders is optimized, the film thickness is increased, and the oxidation resistance and conductivity are improved. In addition, by rationally selecting organic additives and exerting their effects, the screen printing performance of the silver paste is improved while increasing the film thickness. During the high-temperature sintering process, the organic matter in the silver paste decomposes and volatilizes, so that the metal silver powder and glass powder are firmly attached to the surface of the glass substrate, realizing the heating and conductive functions. The glass powder acts as a binder and is located between the glass substrate and the metal silver powder, while the metal silver powder is embedded in the glass powder with gaps of different sizes. The selection and matching of this silver powder determines the surface morphology of the silver paste and affects the oxidation resistance of the silver layer.
[0029] The ratio of glass powder to silver powder also affects the adhesion and oxidation resistance of silver paste. When the glass powder content is high, the contact area between silver powder and air is reduced, which delays the oxidation process of the silver layer. In short, the present invention improves the performance of silver paste by optimizing the combination of silver powder and the use of organic additives, and enhances its oxidation resistance and conductivity.
[0030] The anti-oxidation silver paste for automobile glass prepared by the present invention not only meets the basic performances of conductivity, adhesion and matching with black glaze, but also solves the disadvantage of blackening after oxidation of the conventional conductive silver paste for automobile glass, and improves its anti-oxidation property in harsh environment. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0032] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0033] Example 1
[0034] (1) Prepare 100g of material according to the following composition and mass:
[0035]
[0036] The particle size of the spherical silver powder used is 1.5 μm, and the tap density is 6.3 g / mL; the particle size of the flake silver powder is 6 μm, and the tap density is 2.5 g / mL;
[0037] The average particle size of the glass powder 1# used is about 2μm, and its components and percentages are: 28% silicon dioxide, 6% niobium pentoxide, 0.5% iron oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, and 7.5% potassium oxide.
[0038] The average particle size of the glass powder 2# used is about 1 μm, and its components and percentages are: 3% titanium dioxide, 5% molybdenum trioxide, 5% cobalt tetroxide, 6% vanadium pentoxide, 68% bismuth trioxide, 4% silicon dioxide, 5% aluminum oxide, and 4% zinc oxide.
[0039] The average particle size of the glass powder 3# used is about 2.5 μm, and its components and percentages are: 11% silicon dioxide, 3% titanium dioxide, 4% mixture of zinc oxide and aluminum oxide (the mass ratio of zinc oxide to aluminum oxide is 1:1), 72% bismuth oxide, 7% boric acid, and 3% lithium carbonate.
[0040] The dispersant used is 0.5 g of polyvinyl alcohol, the thixotropic agent used is 0.1 g of polyamide wax, the leveling agent used is 0.5 g of silicone resin, the polymer resin used is ethyl cellulose, and the organic solvent used is terpineol.
[0041] (2) Preparation of the carrier: Weigh ethyl cellulose and terpineol, then heat them to 80° C. and keep the temperature constant. After the ethyl cellulose is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, thereby obtaining a carrier;
[0042] (3) Preparation of silver paste: Spherical silver powder, flake silver powder, glass powder 1#, glass powder 2#, glass powder 3#, dispersant, thixotropic agent, and leveling agent are weighed, and fully mixed with the carrier in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry;
[0043] (4) Production of silver paste: The above-mentioned paste is ground five times in a three-roll mill, and the fineness of the silver paste is controlled to be below 15 μm and the viscosity is 20-30 Pa·S by fine adjustment of the rollers, thereby obtaining an antioxidant conductive silver paste for automotive glass.
[0044] Example 2
[0045] (1) Prepare 100g of material according to the following composition and mass:
[0046]
[0047] The particle size of the spherical silver powder used is 1.6 μm, and the tap density is 5.8 g / mL; the particle size of the flake silver powder used is 6.5 μm, and the tap density is 2.5 g / mL.
[0048] The average particle size of the glass powder 1# used is about 2μm, and its components and percentages are: 28% silicon dioxide, 6% niobium pentoxide, 0.5% iron oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, and 7.5% potassium oxide.
[0049] The average particle size of the glass powder 2# used is about 1 μm, and its components and percentages are: 3% titanium dioxide, 5% molybdenum trioxide, 5% cobalt tetroxide, 6% vanadium pentoxide, 68% bismuth trioxide, 4% silicon dioxide, 5% aluminum oxide, and 4% zinc oxide.
[0050] The average particle size of the glass powder 3# used is about 2.5 μm, and its components and percentages are: 11% silicon dioxide, 3% titanium dioxide, 4% mixture of zinc oxide and aluminum oxide (the mass ratio of zinc oxide to aluminum oxide is 1:1), 72% bismuth oxide, 7% boric acid, and 3% lithium carbonate.
[0051] The dispersant used is 0.5 polyvinyl alcohol; the thixotropic agent used is 0.1 polyamide wax; the leveling agent used is 0.5 silicone resin; the polymer resin used is ethyl cellulose; and the organic solvent used is terpineol.
[0052] (2) Preparation of the carrier: Weigh ethyl cellulose and terpineol, then heat them to 80° C. and keep the temperature constant. After the ethyl cellulose is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, thereby obtaining the carrier.
[0053] (3) Preparation of silver paste: Spherical silver powder, flake silver powder, glass powder 1#, glass powder 2#, glass powder 3#, dispersant, thixotropic agent, and leveling agent are weighed, and fully mixed with the carrier in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry;
[0054] (4) Production of silver paste: The above-mentioned paste is ground 7 times in a three-roll mill, and the fineness of the silver paste is controlled to be below 15 μm and the viscosity is 20-30 a·s by fine adjustment of the rollers, thereby obtaining an antioxidant conductive silver paste for automotive glass.
[0055] Example 3
[0056] (1) Prepare 100 materials according to the following composition and quality:
[0057]
[0058] The particle size of the spherical silver powder used is 1.6 μm, and the tap density is 5.0 g / mL; the particle size of the flake silver powder is 6.5 μm, and the tap density is 2.5 g / mL;
[0059] The average particle size of the glass powder 1# used is about 2μm, and its components and percentages are: 28% silicon dioxide, 6% niobium pentoxide, 0.5% iron oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, and 7.5% potassium oxide.
[0060] The average particle size of the glass powder 2# used is about 1 μm, and its components and percentages are: 3% titanium dioxide, 5% molybdenum trioxide, 5% cobalt tetroxide, 6% vanadium pentoxide, 68% bismuth trioxide, 4% silicon dioxide, 5% aluminum oxide, and 4% zinc oxide.
[0061] The average particle size of the glass powder 3# used is about 2.5 μm, and its components and percentages are: 11% silicon dioxide, 3% titanium dioxide, 4% mixture of zinc oxide and aluminum oxide (the mass ratio of zinc oxide to aluminum oxide is 1:1), 72% bismuth oxide, 7% boric acid, and 3% lithium carbonate;
[0062] The dispersant used is 0.5 g of polyvinyl alcohol; the thixotropic agent used is 0.1 g of polyamide wax; the leveling agent used is 0.5 g of silicone resin; the polymer resin used is ethyl cellulose; and the organic solvent used is terpineol.
[0063] (2) Preparation of the carrier: Weigh ethyl cellulose and terpineol, then heat them to 80° C. and keep the temperature constant. After the ethyl cellulose is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, thereby obtaining a carrier;
[0064] (3) Preparation of silver paste: Spherical silver powder, flake silver powder, glass powder 1#, glass powder 2#, glass powder 3#, dispersant, thixotropic agent, and leveling agent are weighed, and fully mixed with the carrier in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry;
[0065] (4) Production of silver paste: The above-mentioned paste is ground 7 times in a three-roll mill, and the fineness of the silver paste is controlled to be below 15 μm and the viscosity is 20-30 Pa·S by fine adjustment of the rollers, thereby obtaining an antioxidant conductive silver paste for automotive glass.
[0066] Example 4
[0067] (1) Prepare 100g of material according to the following composition and mass:
[0068]
[0069]
[0070] The particle size of the spherical silver powder used is 1.6 μm, and the tap density is 5.0 g / mL; the particle size of the flake silver powder is 6.5 μm, and the tap density is 2.5 g / mL;
[0071] The average particle size of the glass powder 1# used is 2μm, and its components and percentages are: 28% silicon dioxide, 6% niobium pentoxide, 0.5% iron oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, and 7.5% potassium oxide.
[0072] The average particle size of the glass powder 2# used is 1 μm, and its components and percentage content are: 3% titanium dioxide, 5% molybdenum trioxide, 5% cobalt tetroxide, 6% vanadium pentoxide, 68% bismuth trioxide, 4% silicon dioxide, 5% aluminum oxide, and 4% zinc oxide.
[0073] The average particle size of the glass powder 3# used is 2.5 μm, and its components and percentage content are: 11% silicon dioxide, 3% titanium dioxide, 4% mixture of zinc oxide and aluminum oxide (the mass ratio of zinc oxide to aluminum oxide is 1:1), 72% bismuth oxide, 7% boric acid, and 3% lithium carbonate.
[0074] The dispersant used is 0.5 g of polyvinyl alcohol; the thixotropic agent used is 0.1 g of polyamide wax; the leveling agent used is 0.5 g of silicone resin; the polymer resin used is ethyl cellulose; and the organic solvent used is terpineol.
[0075] (2) Preparation of the carrier: Weigh ethyl cellulose and terpineol, then heat them to 80° C. and keep the temperature constant. After the ethyl cellulose is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, thereby obtaining a carrier;
[0076] (3) Preparation of silver paste: Spherical silver powder, flake silver powder, glass powder 1#, glass powder 2#, glass powder 3#, dispersant, thixotropic agent, and leveling agent are weighed, and fully mixed with the carrier in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry;
[0077] (4) Production of silver paste: The above-mentioned paste is ground 7 times in a three-roll mill, and the fineness of the silver paste is controlled to be below 15 μm and the viscosity is 20-30 Pa·S by fine adjustment of the rollers, thereby obtaining an antioxidant conductive silver paste for automotive glass.
[0078] Example 5
[0079] (1) Prepare 100g of material according to the following composition and mass:
[0080]
[0081]
[0082] The particle size of the spherical silver powder used is 1.6 μm, and the tap density is 5.0 g / mL; the particle size of the flaky silver powder is 6.5 μm, and the tap density is 2.5 g / mL.
[0083] The average particle size of the glass powder 1# used is 2μm, and its components and percentages are: 28% silicon dioxide, 6% niobium pentoxide, 0.5% iron oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, and 7.5% potassium oxide.
[0084] The average particle size of the glass powder 2# used is 1 μm, and its components and percentage content are: 3% titanium dioxide, 5% molybdenum trioxide, 5% cobalt tetroxide, 6% vanadium pentoxide, 68% bismuth trioxide, 4% silicon dioxide, 5% aluminum oxide, and 4% zinc oxide.
[0085] The average particle size of the glass powder 3# used is 2.5 μm, and its components and percentage content are: 11% silicon dioxide, 3% titanium dioxide, 4% mixture of zinc oxide and aluminum oxide (the mass ratio of zinc oxide to aluminum oxide is 1:1), 72% bismuth oxide, 7% boric acid, and 3% lithium carbonate.
[0086] The dispersant used is 0.5 g of polyvinyl alcohol; the thixotropic agent used is 0.1 g of polyamide wax; the leveling agent used is 0.5 g of silicone resin; the polymer resin used is ethyl cellulose; and the organic solvent used is terpineol.
[0087] (2) Preparation of the carrier: Weigh ethyl cellulose and terpineol, then heat them to 80° C. and keep the temperature constant. After the ethyl cellulose is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, thereby obtaining a carrier;
[0088] (3) Preparation of silver paste: Spherical silver powder, flake silver powder, glass powder 1#, glass powder 2#, glass powder 3#, dispersant, thixotropic agent, and leveling agent are weighed, and fully mixed with the carrier in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry;
[0089] (4) Production of silver paste: The above-mentioned paste is ground 7 times in a three-roll mill, and the fineness of the silver paste is controlled to be below 15 μm and the viscosity is 20-30 Pa·S by fine adjustment of the rollers, thereby obtaining an antioxidant conductive silver paste for automotive glass.
[0090] The performance of the anti-oxidation conductive silver paste for automobile glass prepared in Examples 1 to 5 above was tested, and the results are shown in Table 1:
[0091] Table 1
[0092]
[0093] In summary: Through Examples 1-5, it can be concluded that the combination of silver powders with different tap densities has different effects on the performance of silver paste. Under the same condition of flaky silver powder, as the tap density of spherical silver powder continues to increase, its antioxidant performance and matching with black glaze are relatively excellent, its resistance continues to decrease, its conductivity is improved, and its welding strength is also continuously increased.
[0094] The silver paste prepared by the present invention, on the whole, not only has excellent anti-oxidation performance, but also has certain advantages in electrical conductivity, matching with black glaze and welding strength.
[0095] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An anti-oxidation conductive silver paste for automotive glass, characterized in that: The raw materials use the following components and weight percentages: Spherical silver powder 50-80%, flake silver powder 8-10%; glass powder 1# 0.5-2.0%, glass powder 2# 0.5-2.0%, glass powder 3# 1.0-2.0%; dispersant 0.3-1%; thixotropic agent 0.1-0.5%; leveling agent 0.5-1.0%; polymer resin 2-10%; organic solvent 5-25%.
2. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The particle size of the spherical silver powder is 0.5-3.0 μm, and the tap density is 5.0-7.0 g / mL; The particle size of the flaky silver powder is 4-12 μm, and the tap density is 1.0-3.0 g / mL.
3. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The glass powder 1# is lead-free glass powder with a particle size of 1.2-3.3 μm, including the following components and weight percentages: 28% silicon dioxide, 6% niobium pentoxide, 0.5% iron oxide, 8% sodium oxide, 13% boron oxide, 9.5% zinc oxide, 3% bismuth oxide, 9% titanium oxide, 1.5% manganese trioxide, 3.5% zirconium oxide, 4% yttrium oxide, 3% aluminum oxide, 3.5% lithium oxide, and 7.5% potassium oxide.
4. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The glass powder 2# is lead-free glass powder with a particle size of 0.5-2.1 μm, and includes the following components and weight percentages: 3% titanium dioxide, 5% molybdenum trioxide, 5% cobalt tetroxide, 6% vanadium pentoxide, 68% bismuth trioxide, 4% silicon dioxide, 5% aluminum oxide, and 4% zinc oxide.
5. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The glass powder 3# is lead-free glass powder with a particle size of 2.0-3.0 μm, including the following components and weight percentages: 11% silicon dioxide, 3% titanium dioxide, 4% a mixture of zinc oxide and aluminum oxide, 72% bismuth oxide, 7% boric acid, and 3% lithium carbonate, wherein the mass ratio of zinc oxide to aluminum oxide in the 4% mixture of zinc oxide and aluminum oxide is 1:
1.
6. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The polymer resin is selected from any one or more of ethyl cellulose, nitro cellulose and ethyl hydroxyethyl cellulose.
7. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The dispersant is selected from any one or more of polyvinyl alcohol, sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, tributyl phosphate, oleic acid, stearic acid and n-octanoic acid.
8. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The thixotropic agent is selected from any one or more of organic bentonite, modified polyurea compounds, fumed silica, acrylic resin, and polyamide wax.
9. The anti-oxidation conductive silver paste for automobile glass according to claim 1, characterized in that: The leveling agent is selected from any one or more of silicone resin, hydrogenated castor oil, polyvinyl butyral, and polyacrylate; The organic solvent is selected from any one of terpineol, turpentine, diethylene glycol butyl ether, diethylene glycol dibutyl ether, butyl carbitol acetate or a mixture of several thereof.
10. A method for preparing an anti-oxidation conductive silver paste for automobile glass according to any one of claims 1 to 9, characterized in that: The steps include: S1. Prepare the materials according to the following components and weight percentages: Spherical silver powder 50-80%, flake silver powder 8-10%; glass powder 1# 0.5-2.0%, glass powder 2# 0.5-2.0%, glass powder 3# 1.0-2.0%; dispersant 0.3-1%; thixotropic agent 0.1-0.5%; leveling agent 0.5-1.0%; polymer resin 2-10%; organic solvent 5-25%; S2. Preparation of carrier: Weigh the polymer resin and the organic solvent, and then heat them to 80°C and keep the temperature constant. After the polymer resin is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, and obtain the carrier; S3, preparation of silver paste: weigh spherical silver powder, flaky silver powder, glass powder 1#, glass powder 2#, glass powder 3#, dispersant, thixotropic agent, leveling agent, and fully mix with the carrier in a mixer, and then use a high-speed dispersant for high-speed dispersion to obtain a uniform slurry; S4. Production of silver paste: Grind the above slurry in a three-roll mill, and fine-tune the fineness of the silver paste to below 15 μm and the viscosity to 20-30 Pa·S by rollers, so as to prepare an antioxidant conductive silver paste for automotive glass.
Citation Information
Patent Citations
Lead-free silver slurry for high-temperature sintered automobile glass heating wire and preparation method thereof
CN101613186A
Cited By
Novel smart phone flexible printed circuit board and module prepared based on weldable silver paste
CN121001267A
Antioxidant conductive silver paste for automotive glass and preparation method therefor
WO2026143977A1